1992
DOI: 10.1037/h0079314
|View full text |Cite
|
Sign up to set email alerts
|

Family reunification following shelter placement: Child, family, and program correlates.

Abstract: Factors associated with family reunification following a short-term stay in a shelter for runaway and troubled youth were examined. Children who were not reunified with their caretakers following their stay reported more family problems, appeared to be at higher risk of suicide, and stayed longer in the shelter. Implications for delivery of shelter service programs are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 7 publications
3
24
1
Order By: Relevance
“…The therapist was described to the youth as an ally who may be useful when dealing with family members, probation officers, court appearances, and the school system (Slesnick et al, 2000). As family variables are identified by youth as being of most concern when they are removed from the home (Teare et al, 1992), and the failure to have a supportive family may be the single largest factor associated with adolescent homelessness (Rotheram-Borus, 1991). It follows that family variables, rather than drug use variables, would be most predictive of family therapy attendance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The therapist was described to the youth as an ally who may be useful when dealing with family members, probation officers, court appearances, and the school system (Slesnick et al, 2000). As family variables are identified by youth as being of most concern when they are removed from the home (Teare et al, 1992), and the failure to have a supportive family may be the single largest factor associated with adolescent homelessness (Rotheram-Borus, 1991). It follows that family variables, rather than drug use variables, would be most predictive of family therapy attendance.…”
Section: Discussionmentioning
confidence: 99%
“…Teare, Furst, Peterson, & Authier (1992) reported that in their sample of shelter runaways, youths' greatest needs included living arrangements, family relationships, and communication with parents. Also, those youth not reunified with their family had higher levels of hopelessness, suicide ideation, and reported more family problems than those reunified.…”
mentioning
confidence: 99%
“…' Cameron and Karabanow (2003) cited anecdotal evidence that family interventions appear preferable to individual therapy in addressing adolescent emotional and behavioral problems, specifically noting a marked reduction in illicit drug use, conduct disorders, family conflicts, and the amount of time spent in institutions for those youth engaged in family interventions. Using self-report data from the suicide probability scale (Cull & Gill, 1982), Teare, Furst, Peterson, and Authier (1992) found that shelter Family Therapy and Reunification Ballantyne & Raymond, 1998;Bronstein, 1996;Cameron & Karabanow, 2003;Hawkins & Fraser, 1983;Kidd, 2003;Teare, Furst, Peterson, & Authier, 1992;Tolan & Loeber, 1993 YouthCare family reconciliation services (Ray & Roloff, 1993) Seek to reduce conflict between parents and youth Intervention with family members in addition to the youth to help families cope and remain intact (Robertson & Toro, 1999;Teare et al, 1994) Focus on reuniting and developing relationships between parents and street youth Common for shelters to attempt family reunification Rigorous assessment of potential for family reunification should be performed before reuniting youth with family members (Kidd, 2003) McCarthy and Hagan (1992) (Schorr, 1997) Partners in Denver (Hawkins & Fraser, 1983;Wall, Hawkins, Lishner & Fraser, 1981) Project Wincroft (Hawkins & Fraser, 1983;Smith, Farrant, & Marchant, 1972) Pairing of a troubled youth with a role model Street youth build positive, long-term relationships Focus on characteristics and qualities that mentors provide that lead to street youth's resilience Mentors and youth should share cultural and racial characteristics (Cameron & Karabanow, 2003) Evidence of decrease in youth crime rate Mentors provide stability and an opportunity for youth to talk in a nonjudgmental setting and have positive social interactions Some evidence of improved employment Mentoring turnover can be high (Cameron & Karabanow, 2003) Difficult to train and pair mentors with youth (...…”
Section: Family Therapy and Reunificationmentioning
confidence: 99%
“…Teare, Furst, Peterson, and Authier (1992) found that in their sample of shelter youths, those not reunified with their family were at greater risk of suicide, had more overall dissatisfaction with life, greater hopelessness, more generalized negative expectations about the future and more family problems compared to those who were reunified. Thus, attention towards reunifying families whose child resides at a shelter (when appropriate), or addressing problematic family interaction patterns prior to the youth leaving home, is worthy of future research focus.…”
Section: Future Directionsmentioning
confidence: 99%